Migration of Field Rodents due to Poison-Baiting - Pasahan, S C; Sabhlok, V P (Annals of Arid Zone, 2016)
The present information comprises the results achieved as a result of theerror in control success due to migration of rodent on the deployment of arodenticide. Murids are found to be highly mobile in the fields and theirrange Of migration fell between 40.0 m and 76.3 m. Single exposure ofBromadiolone/Brodifacoum has kept the anticoagulants at an edge over inrodent control levels. Migration in rodents has been found occurring as aconsequence of the communication brought about by the victimised animals.